PELATIHAN DIGITAL MARKETING UNTUK UMKM YANG ADA DI DESA BULANGAN KECAMATAN GRESIK - Latifah, Eny; Abdullah, Rudi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
The aim of this community service is to provide training to MSMEs (PKK's main target) in Bulangan Village, Gresik Regency. The service method used is Participatory Action Research (PAR) which is to provide learning in overcoming a problem. The result of the service is the socialization of digital marketing by introducing e-commerce and how to create it. Providing training on the CANVA application platform in designing MSME product logos. The achievement achieved by MSMEs or PKK is that they already have an e-commerce account and are ready to buy and sell digitally.